ISLAMIC WEALTH MANAGEMENT ASURANSI SYARIAH SEBAGAI INSTRUMEN PROTEKSI KEKAYAAN Studi Kasus pada HNWI - , Edi Dwi Efendi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis is a case study on clients who clasified as HNWI (high net worth individual) and have problems in the management of wealth due to time constraints and lack of knowledge. In this study, the analysis focused on the first pillar of wealth management (protection and preservation of wealth) with consideration of clientâs financial goals is for the children to be able to achieve the university level, maintaining the family in case of disability and preserving the family living if he died. The risks that clients have are the risk of death, the risk of temporary incapability to work, the risk can not work forever, the risk of illness and catastrophe risk to property. These risks are analyzed, whether the client anticipated risk with proper and adequate instrument. Base on the results of the analysis, then the client is given advice on protection againts the risks that exist with the use of sharia insurance instrument. The analysis showed that clients do not anticipate any risks with the right tools and adequate. To clients recommended to use a variety of sharia-compliant insurance product that can be used to anticipate the risk of death, the risk of temporary incapability to work, the risk can not work forever, the risk of illness and catastrophe risk to property.